Świat wartości swoich i obcych w Krzyżakach Henryka Sienkiewicza - Mariak, Leonarda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article discusses the linguistic devices of the evaluation of the characters created in the realities of the novel (fictitious and historical) connected with two opposite groups: the Poles (domestic) and the Teutonic Knights (foreign). The analysis of the material has revealed the persuasive mechanisms applied by Henryk Sienkiewicz in order to exert influence on the readers’ attitudes and their system of values. The repertoire of linguistic and semantic devices used for evaluation is very diversified and, among others, includes: synonymic passages giving names to the representatives of both groups, the names of values (positive or negative) and the phrases describing actions, character features and people’s attitudes evaluated as positive or negative, connecting synonymous names (of Poles and the Teutonic Knights) with different parts of speech; statements with specific connotations (positive or negative) informing about the actions, behaviours and appearance of the characters; stylistic means such as: similes, metaphors, epithets used in an expressive and evaluating function. Additionally, the conclusions drawn from the research shed light on Henryk Sienkiewicz’s writing techniques. It has become feasible to reconstruct (indirectly) the writer’s attitudes towards life and the system of values.